The Dynamics of Education of Mlangi Community in Yogyakarta: from Pesantren Education to Formal Education - Sasadara, Sasadara; Fakhiroh, Shofa; Setiawan, Agung (Graduate School of UIN Syarif Hidayatullah Jakarta, 2022)
The life of Javanese society in general is heavily influenced by the culture and the values of pesantren. For some Javanese who fall into the category of santri, their education cannot be separated from the world of pesantren. This also happens in Mlangi community, where they are also part of santri who study at pesantren. But as the time progresses and the time changes, the people of Mlangi also began to pursue formal education in their lives. This research uses the concept of dynamics and of modernization with historical research methods. The theory used is of evolution by Herbert Spencer. Spencer said that the evolution occurring in a society is based on the types of society in question. The typology of society developed by Spencer is a simple society and a pluralistic society. The historical research method consists of heuristics, verification, interpretation, and historiography. The study found that Mlangi community initially feel that religious education alone is sufficient. After modernization, they feel that formal education is also important in addition to the religious education obtained at pesantren. This is due to their evolving mindset due to modernization. In 2001, many parents started sending their children to several pesantren in Mlangi. In addition to studying at pesantren, they also want to study in formal schools because of the demands of an increasingly modern era. They want balance between the world and the hereafter.